A Potemkin state in the Sahel? The empirical and the fictional in Malian state reconstruction. Issue 1 (2nd January 2018) - Craven-Matthews, Catriona; Englebert, Pierre
ABSTRACT: Despite significant reconstruction efforts in the wake of its 2012–2013 collapse, Mali remains mired in crisis: violence is on the rise, institutions are dysfunctional, the military is inefficient, investments are few, and corruption is rampant. We suggest that Mali's reconstruction's failure is but the latest iteration of a general failure at building the Malian state. This failure derives from a sheer lack of resources to sustain statehood and from a systematic tendency to emulate the French state model despite its incongruence with local conditions. As a result, the Malian state is mimicked more than it is built and its reconstruction imagined more than it is implemented. Conflict plays an important role in this production, as it presents Mali with significant opportunities to stage itself, to develop and multiply institutions, and to derive outside support. Evocations of Mali's precolonial imperial past, meant to provide cover and legitimacy to its leadership, further disconnect the state from the realities of modern governance. The enactment of reconstruction is not, however, irrational for leaders with few short-run alternatives or for international partners eager to engage local security threats. There might be other alternatives, however, with greater potential for embedding the state into local resources, populations, and practices. Exploring opportunities for a greater adjunction of Islamic governance and for decentralization reforms more genuinely predicated on local institutions of collective action might prove fruitful.